Epidemiological Situation on Rickettsial Diseases and Q Fever in the Russian Federation over the Period of 2010–2023, Forecast for 2024 - S. V. Shtrek; N. V. Rudakov; S. N. Shpynov; A. I. Blokh; D. V. Trankvilevsky; N. A. Pen’evskaya; L. V. Kumpan; A. V. Sannikov (Проблемы особо опасных инфекций)
The aim of the review is to forecast the incidence of rickettsial infections and Q fever in the Russian Federation for 2024 based on an analysis of the epidemiological situation in 2010–2023. The epidemic potential associated with these infections in Russia and other countries where there is an increased activity of foci with an expansion of the area of pathogen circulation has been assessed. An analysis of the incidence of epidemic typhus, Brill’s disease, Siberian tick-borne typhus (STT), Astrakhan spotted fever (ASF), Q fever, human granulocytic anaplasmosis, human monocytic ehrlichiosis in the Russian Federation in 2023 in comparison with long-term average values in 2010–2019 (COVID-19 pre-pandemic period) has been carried out. In 2023, the rates of registered incidence of rickettsial infections and Q fever in Russia as a whole decreased relative to the long-term average level of 2010–2019, and there is a significant downward trend in most regions. The exception is the Far Eastern Federal District, where the incidence rate of STT in 2023 increased by 1.5 times as compared to the period of 2010–2019, and the city of Sevastopol, where an increase in the incidence of Marseilles fever was detected. When assessing the intra-annual distribution of incidence in 2023, registration of STT in Russia was carried out from March to November inclusive, ASF – from May to October, and Q fever – from May to August.